Microbial Small Talk: Volatiles in Fungal–Bacterial Interactions - Schmidt, Ruth; Etalo, Desalegn W.; de Jager, Victor; Gerards, Saskia; Zweers, Hans; de Boer, Wietse; Garbeva, Paolina (Frontiers in Microbiology, 2016)
There is increasing evidence that volatile organic compounds (VOCs) play an important role in the interactions between fungi and bacteria, two major groups of soil inhabiting microorganisms. Yet, most of the research has been focused on effects of bacterial volatiles on suppression of plant pathogenic fungi whereas little is known about the responses of bacteria to fungal volatiles. In the current study we performed a metabolomics analysis of volatiles emitted by several fungal and oomycetal soil strains under different nutrient conditions and growth stages. The metabolomics analysis of the tested fungal and oomycetal strains revealed different volatile profiles dependent on the age of the strains and nutrient conditions. Furthermore, we screened the phenotypic responses of soil bacterial strains to volatiles emitted by fungi. Two bacteria, Collimonas pratensis Ter291 and Serratia plymuthica PRI-2C, showed significant changes in their motility, in particular to volatiles emitted by Fusarium culmorum. This fungus produced a unique volatile blend, including several terpenes. Four of these terpenes were selected for further tests to investigate if they influence bacterial motility. Indeed, these terpenes induced or reduced swimming and swarming motility of S. plymuthica PRI-2C and swarming motility of C. pratensis Ter291, partly in a concentration-dependent manner. Overall the results of this work revealed that bacteria are able to sense and respond to fungal volatiles giving further evidence to the suggested importance of volatiles as signaling molecules in fungal–bacterial interactions.